Clinical and Prognostic Relevance of B7-H3 and Indicators of Glucose Metabolism in Colorectal Cancer - Zhang, Ting; Jin, Yufen; Jiang, Xin; Li, Longhai; Qi, Xiaowei; Mao, Yong; Hua, Dong (Frontiers in Oncology, 2020)
Objective This study aimed to investigate the clinical and prognostic relevance of B7-H3 expression and indicators of glucose metabolism in patients with colorectal cancer (CRC). Methods Using immunohistochemistry, the expression of B7-H3 was detected in a total of 213 formalin-fixed paraffin-embedded CRC tissue specimens. Furthermore, levels of fasting blood glucose (FBG), lactic dehydrogenase (LDH) and fructosamine (FMN) as indicators of glucose metabolism were also analyzed in patients with CRC, and stratified into the high or low expression sub-groups based on Youden Index. The relationship between B7-H3, FBG, LDH, FMN expression, and clinicopathological characteristics were also evaluated to establish their prognostic significance in patients with CRC. Results B7-H3 was highly expressed in CRC tissue. The positive rates of B7-H3 expression was 63.8% (136/213). We found a linear correlation between B7-H3 and FBG in depth of tumor invasion (T3/4) (p=0.037, r=0.259), lymph node metastasis (N0) (p=0.004, r=0.259) and TNM stage (I/II) (p=0.009, r=0.242). High expression of FBG, LDH, FMN [hazard ratio (HR)=1.916, 95% CI: 1.223-3.00, p=0.005; HR=1.801, 95% CI: 1.153-2.813, p=0.010; HR=2.154, 95% CI: 1.336-3.472, p=0.002], respectively, was identified as a significant independent predictor of poor overall survival (OS). Although B7-H3 expression did not affect OS, CRC patients expressing both high B7-H3 and high FMN contributed to a significant decrease in OS (HR=1.881, 95%CI: 1.059-3.339, p=0.031). Moreover, with low expression of B7-H3, high expression of FBG, LDH and FMN were also recognized as predictors of inferior OS (HR=3.393, 95% CI: 1.493-7.709, p=0.004; HR=7.107, 95% CI: 2.785-18.138, p=0.000; HR=2.800, 95% CI: 1.184-6.625, p=0.019). Conclusion B7-H3 combined with FBG, LDH or FMN could reflect the clinical outcomes of patients with CRC.